2024
DOI: 10.1039/d3mh01292a
|View full text |Cite
|
Sign up to set email alerts
|

The emergence and prospects of carbon dots with solid-state photoluminescence for light-emitting diodes

Ting Yuan,
Qian Teng,
Chenhao Li
et al.

Abstract: The significant features emerging from carbon dots (CDs), such as bright and tunable photoluminescence, high thermal stability, and low toxicity, have shown tremendous potential for next generation optoelectronics. Despite great...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 100 publications
0
3
0
Order By: Relevance
“…In recent years, researchers have extensively studied the fluorescence characteristics and mechanisms of CDs, resulting in significant achievements. 52–54 However, the investigation into the RTP mechanism of CDs remains at an early stage of development. Further exploration of the RTP luminescence mechanism of CDs is crucial for adjusting the visible-light-excited RTP characteristics of CDs.…”
Section: Luminescence Mechanisms Of Visible-light-excited Rtp CD Mate...mentioning
confidence: 99%
“…In recent years, researchers have extensively studied the fluorescence characteristics and mechanisms of CDs, resulting in significant achievements. 52–54 However, the investigation into the RTP mechanism of CDs remains at an early stage of development. Further exploration of the RTP luminescence mechanism of CDs is crucial for adjusting the visible-light-excited RTP characteristics of CDs.…”
Section: Luminescence Mechanisms Of Visible-light-excited Rtp CD Mate...mentioning
confidence: 99%
“…The limited space of electronics makes it difficult to efficiently export heat, resulting in a significant temperature rise in electronics. Related studies have shown that the reliability and service life of electronics will decrease with high temperature and even lead to electronics failure [4,5]. Therefore, developing new and efficient thermal management technologies to achieve effective heat dissipation in electronics is an urgent issue that needs to be addressed [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous methods, typically top-down and bottom-up methods, are extensively investigated for developing miscellaneous CDs and catering to a wide range of applications. [1][2][3][4][5][6] CDs-based electroluminescent light-emitting diodes (LEDs) are highly spotlighted due to their attractive merits such as rich carbon sources, low-cost solution processability, and environment-friendly characteristics excluding toxic Cd and Pb, and universal modification by surface treatment and chemical bonding, showing potential applications in new-generation displays and lighting. For assembling CD-based LEDs, one uses CDs as emitters by constructing multilayer electroluminescent devices, while the other uses photoluminescence (PL) characteristics of CDs pumped by conventional GaN-based UV or blue LED chips.…”
Section: Introductionmentioning
confidence: 99%